2021
DOI: 10.46481/jnsps.2021.261
|View full text |Cite
|
Sign up to set email alerts
|

Waste glass: An excellent adsorbent for crystal violet dye, Pb2+ and Cd2+ heavy metals ions decontamination from wastewater

Abstract: The suitability of waste glass as an eco-friendly adsorbent for the removal of crystal violet (CV) dye, Pb2+ and Cd2+ heavy metal ions in waste water samples was investigated in batch mode. Waste glass sample was pulverized and characterized by SEM/EDX, XRD, BET and FTIR. Effects of variation in temperature, pH, contact time and recyclability of the adsorbent were studied. FTIR spectra revealed major peaks around 491.53 and 3444.12 cm-1 corresponding to the bending vibrations of Si-O-Si and -OH groups respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The heat of adsorption does not depend on the number of sites and is equal for all sites. The linearised form of the Langmuir model as described by Sodeinde et al 25 is shown in Eq. ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The heat of adsorption does not depend on the number of sites and is equal for all sites. The linearised form of the Langmuir model as described by Sodeinde et al 25 is shown in Eq. ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each composite is made of 5 grab samples randomly collected from each area of the rice farm. In the same way, twelve (12) composite soil samples were collected after the rice harvest. Four (4) grab samples were randomly collected from different parts of the land which has not undergone any agricultural practice (a fallow land) as the soil control.…”
Section: Soil Sample Collectionmentioning
confidence: 99%
“…Twelve (12) composite rice plant samples were collected from four different sections of the farm. Each composite consists of five (5) randomly selected rice plants concerning the soil already sampled.…”
Section: Rice Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations